2014
DOI: 10.1007/s10725-014-9950-8
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of abscisic acid and indole-3-acetic acid during the early-middle stage of seed development in Rosa hybrida

Abstract: Concentrations of endogenous abscisic acid (ABA) and indole-3-acetic acid (IAA) in Rosa hybrida seed coat and embryos were determined at 28, 35, 42, and 49 days after pollination (DAP), a period encompassing the early-middle stages of seed development. No studies on rose have ever documented simultaneous change in ABA and IAA during these developmental phases in both seed coat and embryo. Plant growth regulators were extracted and then quantified by using high performance liquid chromatography based on solid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…Our results revealed that the ABA content increased as the seed approach maturation, peaking at 14.6 ng/g. The dynamic change of ABA content in P. armeniacum seed was similar to that of Rosa hybrida , Pinus taeda , and other species [ 33 , 34 ]. There is the possibility that the high level of ABA in the early stage can inhibit the premature germination of seeds [ 35 ].…”
Section: Discussionsupporting
confidence: 53%
“…Our results revealed that the ABA content increased as the seed approach maturation, peaking at 14.6 ng/g. The dynamic change of ABA content in P. armeniacum seed was similar to that of Rosa hybrida , Pinus taeda , and other species [ 33 , 34 ]. There is the possibility that the high level of ABA in the early stage can inhibit the premature germination of seeds [ 35 ].…”
Section: Discussionsupporting
confidence: 53%
“…2, the ABA content in loquat seeds on the day of harvest ranged greatly between cultivars from 42.76 ng • g -1 FW ('Ninghaibai') to 81.61 ng • g -1 FW ('Oobusa'). The content is lower than those reported for some other Rosaceae plant seeds, e.g., 0.55 pmol • mg -1 (equals to 145.20 ng • g -1 FW) for rose (Rosa hybrida) (Bosco et al, 2015) and 354.65 ng • g -1 FW for 'Cuiguan' sand pear (Pyrus pyrifolia) (Wang et al, 2013). The relatively low content of ABA in loquat seeds might be related to the lack of obvious dormancy in contrast to the obvious seed dormancy in rose and sand pear (Pipino et al, 2013;Wang et al, 2013).…”
Section: Resultsmentioning
confidence: 54%
“…Seeds are mainly used for propagation of rose species, for the production of rootstocks, and in plant breeding to obtain new cultivars (Horn 1992, Pipino et al 2011, Pipino et al 2013, Bosco et al 2015. Ornamental roses are usually propagated by budding or bench-grafting onto rootstocks (Short and Roberts 1991).…”
Section: Introductionmentioning
confidence: 99%